2014
DOI: 10.1177/0004563214542471
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the in vitro stability of commonly measured vitamins and carotenoids in whole blood

Abstract: Background: The pre-analytical stabilities of vitamins A, E, K, B1, B2, B6, B12, C, carotenoids and folates in whole blood were studied. The aim of this work was to provide clear and workable pre-analytical procedures specifying optimal delay before freezing for laboratories which perform themselves such analyses or which receive and transfer such specimens to referral laboratories. Methods: The stability of vitamins was studied in whole blood at room temperature after light exposure up to 24 h (vitamin C), 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…A study that has looked at storage of several analytes up to a maximum of 96 h at 21°C CRP, retinol, and ferritin was reported to be stable; the mean concentration of folic acid however changed significantly over time, with the sharpest decrease (8.7%) in the first 2 h of storage ( 21 ). Vitamins A, E, K, B1, B2, B12, RBC folate and carotenoids were shown to be stable in whole blood when stored refrigerated or at RT even up to 48 or 72 h. Serum folic acid showed clinically and statistically significant changes in mean concentration after delayed centrifugation ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study that has looked at storage of several analytes up to a maximum of 96 h at 21°C CRP, retinol, and ferritin was reported to be stable; the mean concentration of folic acid however changed significantly over time, with the sharpest decrease (8.7%) in the first 2 h of storage ( 21 ). Vitamins A, E, K, B1, B2, B12, RBC folate and carotenoids were shown to be stable in whole blood when stored refrigerated or at RT even up to 48 or 72 h. Serum folic acid showed clinically and statistically significant changes in mean concentration after delayed centrifugation ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have previously emphasised the importance of the collection and processing method for maintaining ascorbate stability in blood samples, with temperature and pH being the most important factors, particularly with respect to the anticoagulant used and perhaps also the acid precipitant, although the latter is less clear [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Our review of the literature of DHA concentrations reported in clinical cohorts (summarized in Table 3 ) has also highlighted that high concentrations of DHA are observed in all studies (except one [ 13 ]) that have used colourimetric or flourometric methods for detecting DHA [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data are in agreement with recently published data, albeit which studied stability in lithium heparin plasma as opposed to serum. 17 The LC-MS/MS method was compared to a HPLC-UV assay in routine clinical use, utilizing samples taken from patients on long-term parenteral nutrition support managed within an intestinal failure unit.…”
Section: Discussionmentioning
confidence: 99%